Interfacing Complex Laboratory Instruments during a Change to Epic Beaker - Scott, Gregory David (J Pathol Inform, 2018)
BACKGROUND: Implementing a laboratory-developed test sometimes requires incorporating an unconventional device into the laboratory information system (LIS) and customizing an interface to reduce transcription error and improve turnaround time. Such a custom interface is a necessity for complicated high-volume tests such as 25-OH Vitamin D by liquid chromatography-tandem mass spectrometry (LC-MS/MS) when there is no vendor-or LIS-supplied interface available. Here, we describe our work and experience interfacing a API 5000 LC-MS/MS instrument with our newly implemented LIS, Epic Beaker, using a combination of in-house scripting software and a middleware vendor, Data Innovations. MATERIALS AND METHODS: For input interfacing, custom scripting software was developed to transcribe batched order lists generated by Epic into files usable by the instrument software, Analyst(®). For output interfacing, results from the LC-MS/MS system were fed to a unidirectional instrument driver made by Data Innovations and selected data were transferred to the LIS. RESULTS: Creation and validation of a new driver by Data Innovations took approximately 6 months. The interface was adopted for 25-OH Vitamin D and testosterone testing during periods of increasing test volume (4.5-fold over 8 years and 1.25-fold over 5 years). The amount of time spent reporting 25-OH Vitamin D results decreased 82% per order resulting in a savings of 1370 technician work hours and the amount of time spent reporting testosterone results decreased 75% per order resulting in a savings of 400 technician work hours. CONCLUSIONS: A mixed model using custom scripting and curated commercial middleware serve as a durable interface solution for laboratory instrumentation such as an LC-MS/MS and are flexible to future changes in instrument software, networking protocols, and the scope of LISs and work area managers.